A functional imaging study of cooperation in two-person reciprocal exchange - McCabe, Kevin (The National Academy of Sciences, 2001)
Cooperation between individuals requires the ability to infer each other's mental states to form shared expectations over mutual gains and make cooperative choices that realize these gains. From evidence that the ability for mental state attribution involves the use of prefrontal cortex, we hypothesize that this area is involved in integrating theory-of-mind processing with cooperative actions. We report data from a functional MRI experiment designed to test this hypothesis. Subjects in a scanner played standard two-person “trust and reciprocity” games with both human and computer counterparts for cash rewards. Behavioral data shows that seven subjects consistently attempted cooperation with their human counterpart. Within this group prefrontal regions are more active when subjects are playing a human than when they are playing a computer following a fixed (and known) probabilistic strategy. Within the group of five noncooperators, there are no significant differences in prefrontal activation between computer and human conditions.